Solution Processed Of Solid State HTL Of CuSCN Layer At Low Annealing Temperature For Emerging Solar Cell - Arith, Faiz; Muhammad Mustafa, Ahmad Nizamuddin; Nor, Mohd Khanapiah; Aliyaselvam, Omsri Vinasha; Al-Ani, Oras Ahmed (Gazi Universitesi, 2021)
High density and uniform Hole Transport Layer (HTL) Copper (I) thiocyanate (CuSCN) was prepared directly on Indium-doped Tin Oxide (ITO) substrate through two-step spin coating technique and followed by low temperature annealing process. A new solvent of Monoethanolamine (MEA) with no additive was introduced for the preparation and yet producing a comparable result of HTL for perovskite solar cell application. The CuSCN layer was characterized for its surface morphology, crystallinity and optical features by using Scanning Electron Microscope (SEM), X-Ray Diffraction (XRD) and Ultraviolet-Visible Spectroscopy (UV-Vis) respectively. Furthermore, the resistivity of the layer was also measured by I-V measurement. An optimized annealing temperature of 100 °C is obtained, resulting pristine morphology structure and high conductivity of 77.30 S/m. This paper is the first to report the use of MEA as a solvent for CuSCN layer, showing that the right combination of solvent use and annealing temperature can produce a good CuSCN structure. Thus, being able to produce HTL layers more easily, rapid and at minimal cost, in turn having a positive impact in reducing the cost of solar cell production